Polysaccharide-Based Transdermal Drug Delivery - Jingyuan Li; Hong Xiang; Qian Zhang; Xiaoqing Miao (MDPI AG, 2022)
Materials derived from natural plants and animals have great potential for transdermal drug delivery. Polysaccharides are widely derived from marine, herbal, and microbial sources. Compared with synthetic polymers, polysaccharides have the advantages of non-toxicity and biodegradability, ease of modification, biocompatibility, targeting, and antibacterial properties. Currently, polysaccharide-based transdermal drug delivery vehicles, such as hydrogel, film, microneedle (MN), and tissue scaffolds are being developed. The addition of polysaccharides allows these vehicles to exhibit better-swelling properties, mechanical strength, tensile strength, etc. Due to the stratum corneum's resistance, the transdermal drug delivery system cannot deliver drugs as efficiently as desired. The charge and hydration of polysaccharides allow them to react with the skin and promote drug penetration. In addition, polysaccharide-based nanotechnology enhances drug utilization efficiency. Various diseases are currently treated by polysaccharide-based transdermal drug delivery devices and exhibit promising futures. The most current knowledge on these excellent materials will be thoroughly discussed by reviewing polysaccharide-based transdermal drug delivery strategies.